2023
DOI: 10.1101/2023.02.13.528424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Orthographic deficits but typical visual perceptual processing in Chinese adults with reading disability

Abstract: Visual orthographic deficits have been reported as one of the core deficits in reading disability (RD), however, whether the deficits are orthographic-specific or domain general in all visual processing is still in debate. Hereby, we conducted an fMRI and an EEG study to examine visual orthographic deficits in Chinese adults with RD. In the fMRI study, we found that there was reduced brain activation in the left inferior temporal gyrus and right cuneus gyrus in orthographic processing (lexical minus perceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…Moreover, we extracted the SSVEP signals at the intermodulation frequencies which were considered to reflect the neural activities of interocular competition ( Poggio and Talbot, 1981 ; May et al, 2012 ; Said and Heeger, 2013 ; Katyal et al, 2016 , 2018 ; Du et al, 2023 ). Consistent with previous research ( Govenlock et al, 2008 ; Cai et al, 2020 ; Gu et al, 2020 ; Mersad and Caristan, 2021 ; Song et al, 2023a ; Yan et al, 2023 ), intermodulation responses were identified at the commonly used frequency of 6.75 Hz (f1 + f2), exhibiting a superior response signal. The signal-to-noise ratio (SNR) was calculated by dividing the power at the extracted frequency by the mean power of the 20 surrounding (10 on each side, excluding the immediately adjacent bin) frequency bins ( Zhang et al, 2011 ; Lyu et al, 2020 ; Song et al, 2023b ).…”
Section: Methodssupporting
confidence: 87%
“…Moreover, we extracted the SSVEP signals at the intermodulation frequencies which were considered to reflect the neural activities of interocular competition ( Poggio and Talbot, 1981 ; May et al, 2012 ; Said and Heeger, 2013 ; Katyal et al, 2016 , 2018 ; Du et al, 2023 ). Consistent with previous research ( Govenlock et al, 2008 ; Cai et al, 2020 ; Gu et al, 2020 ; Mersad and Caristan, 2021 ; Song et al, 2023a ; Yan et al, 2023 ), intermodulation responses were identified at the commonly used frequency of 6.75 Hz (f1 + f2), exhibiting a superior response signal. The signal-to-noise ratio (SNR) was calculated by dividing the power at the extracted frequency by the mean power of the 20 surrounding (10 on each side, excluding the immediately adjacent bin) frequency bins ( Zhang et al, 2011 ; Lyu et al, 2020 ; Song et al, 2023b ).…”
Section: Methodssupporting
confidence: 87%